Public Provisioning For Making India Open Defecation Free And The Implication Of Swachh Bharat Mission (Clean India Campaign) (International Journal of Food and Nutritional Sciences, 2022)
A direct correlation exists between the practice of safe sanitation and good health. Unsafe sanitation and the open defecation (OD) are some of the major causes of infectious diseases such as diarrhea, cholera etc. Sanitation and personal hygiene are the matters of public concern in India as an unsafe and inadequate sanitation system exists throughout the country. About half of the population practice OD. To address the sanitation problem and to make India ODF, the Prime Minister of India introduced the Clean India Mission on 2nd October 2014, which is popularly known as Swachh Bharat Mission (SBM) and the targets of this programme were to be achieved by 2019. However, the achievement of ODF India through SBM is in question and the difference between prediction and progress is mismatching. Here in this study, SBM has been examined to know its outcomes and success in the context of providing subsidized toilets in the rural areas and the extent of people switching over to toilets and change in their defecation habits from outdoor to indoor to make India ODF. The issues have been addressed based on the evidence from the field in Odisha.